Duration of Training and the Incidence of Lumbar Hyperlordosis in Balinese Dancers: A Cross-Sectional Study at SMKN 5 Denpasar - Subawanti, Ni Made Ayu Cindy; Putra, I Putu Yudi Pramana; Yasa, I Wayan Putu Sutirta; Indrayani, Agung Wiwiek (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction : Mastering dance techniques requires prolonged training with repeated practice to achieve optimal movement before progressing to the next stage of the dance. Balinese dance involves a unique posture distinct from daily postures, known as cengked, where the chest is pushed forward. This position causes the body to lean more toward the anterior side. This study aims to examine the relationship between the duration of dance training—measured by training duration, frequency, and onset—and the incidence of lumbar hyperlordosis at SMKN 5 Denpasar. Methods : This study employed an analytical observational design with a cross-sectional approach, using purposive sampling for participant selection. A total of 72 participants were included in the study. Data collection involved assessing the duration, frequency, and onset of dance training through a questionnaire and measuring lumbar lordosis curvature using a flexicurve ruler. Results : The Chi-square test showed a p-value of <0.001. Further analysis using the Phi correlation coefficient indicated correlation values of 0.501 for duration, 0.527 for frequency, and 0.616 for onset, suggesting moderate to strong relationships. Conclusion : The findings indicate a significant relationship, with moderate to strong correlations, between the duration, frequency, and onset of dance training and the incidence of lumbar hyperlordosis at SMKN 5 Denpasar. A limitation of this study is using the flexicurve ruler as a measurement tool, as manual assessment may introduce measurement bias. Keywords : lumbar hyperlordosis, dance training, Balinese dancers